العملات الافتراضية تكييفها الفقهي وحكم التعامل بها: البيتكوين نموذجاً - عودة، مراد بن رايق بن رشيد (الجامعة الإسلامية بالمدينة المنورة, 2019)
يقوم هذا البحث على المنهج الوصفي التحليلي، ويهدف إلى: توضيح حقيقة العملات الافتراضية وخصوصا عملة البيتكوين، وتأصيلها للوصول إلى الحكم الشرعي للتعامل بها، وقد خلص الباحث إلى: أن خصائص وشروط النقود لا تتوفر في العملة الافتراضية، ولذا لا يمكن اعتبار العملات الافتراضية ( البيتكوين ) بأنها عملة بالمعنى الحقيقي، اعتبار العملة الافتراضية ( البيتكوين) سلعة مجهولة المصدر وهمية، لا ضامن لها، قائمة على المقامرة والغرر الفاحش، و لما يحيط بها من شبهات ومخاطر على الاقتصاد الشخصي، واقتصاديات الدول، فلا يجوز شراؤها ولا بيعها ولا تداولها، إلى أن ينصلح حالها، ومن أهم توصيات البحث: طرح موضوع العملات الافتراضية على المجامع الفقهية ودراسته بصورة معمقة، للوصول إلى فتوى مفصلة حول التعامل بمثل هذه العملات الافتراضية، ضرورة التنسيق الدولي بخصوص تداول هذه العملات الرقمية، وسن التشريعات والقوانين التي تضبط تداولها بما يكفل حماية اقتصاد الأفراد والدول.
This research is based on the descriptive analytical method, which aims to: clarifying the reality of digital currencies, especially Bitcoin, and to establish it to reach the Islamic ruling in dealing with it. The researcher concluded that the characteristics and conditions of currency are not available in the virtualized currency. And due to that it cannot be considered as a currency in the real sense, considering the virtualized currency (Bitcoin) as an unknown source and an imaginary commodity, which has no a guarantor, is based on gambling and obscene tricked, and to the suspicions and risks to the personal economy, and countries economics surrounding it, makes it unpermissible to purchase, sale or trade with it, until its situation is corrected, the most important recommendations included: to discuss the issue of the virtualized currencies in the jurisprudence councils and to study it thoroughly, in order to reach a detailed fatwa on dealing with such virtualized currencies, the need for international coordination regarding the circulation of these virtualized currencies, and the enactment of legislation and laws that regulate its circulation in order to protect the economy of individuals and countries.
Keywords: الفقه الإسلامي -- التشريع الإسلامي -- الأحكام الفقهية -- الدراسات الإسلامية -- العملات الإفتراضية -- التكييف الفقهي -- البيتكوين -- مستخلصات الأبحاث